PENGARUH KUALITAS TEH, KUANTITAS EKSPOR, DAN NILAI TUKAR TERHADAP NILAI EKSPOR TEH INDONESIA - Wirani, Githa Fajar; Purwanti, Putu Ayu Pramitha (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 9 (2022): VOL11NO 9, SEPTEMBER 2022 [3325-3700], 2022)
Export value is the value of all goods and services traded abroad which is determined by foreign demand. Quality is the level of good or bad goods or services while export quantity is a benchmark for something that is aimed at an amount that can be calculated with certainty, export transactions need to use the exchange rate as a benchmark for international trade processes, this study aims to determine how the influence of quality tea, export quantity, and exchange rate against Indonesian tea export value for the period 1993 - 2019 either simultaneously or partially. In addition, this study aims to determine the most influential variable on tea export value for the period 1993 - 2019 using SPSS. The results of data analysis show that tea quality, export quantity, and exchange rate simultaneously affect the export value of Indonesian tea in 1993 - 2019. The variables of tea quality and export quantity partially have a positive and significant effect on the value of Indonesian tea exports in 1993 - 2019 while the exchange rate variable partially had a negative and significant effect on the value of Indonesian tea exports in 1993 - 2019.